AKTIVITAS ANTIOKSIDAN INFUSED WATER APEL (Malus domestica) - KAYU MANIS (Cinnamon burmannii) DENGAN VARIASI PENAMBAHAN KURMA (Phoenix dactylifera L) DAN LAMA PERENDAMAN - Triyani, Haztien Silmi; Karyantina, Merkuria; Suhartatik, Nanik (JITIPARI (Jurnal Ilmiah Teknologi dan Industri Pangan UNISRI), 2021)
Water, one of the most important elements of the body and one of the macro substances, has the similar role as carbohydrates, fats and proteins for us humans. Humans cannot survive in few days without drinking. Toxins in human body can be cleansed by consuming water regularly. Infused water alternately becomes the another option to encourage people to drink much water. Furthermore, infused water can help out many people who do not have time or do not like eating fruits. However, many people do not drink water because of their personal reason although infused water might become the second opinion after pure water, and can increase an appetite because of the fruit color. Based on the reason above, the research purposes were appointed to examine the effect of the added date palm and soaking time towards the levels of anti-oxidant in apple-cinnamon infused water. The study was conducted using a Completely Randomized Design (CRD) factorial with 2 factors. In the first factor, the research media was added with dates (0, 10, and 20 grams), and the second factor, the media was measured from its soaking time (4, 8, and 12 hours). The research was initiated by creating of apple-cinnamon infused water with the aadditional various dates. Then, conducting various analyses like chemical analysis, total sugar content analysis, vitamin C, DPPH and FRAP antioxidant activity, total phenol, total solids, and pH. The optimum result was emerged when the additional 10 gram of dates and 4 hours of immersion time were combined. The characteristics of infused water are total sugar 24.37%, vitamin C 11.39 mg / 100 ml, 34.82% RSA DPPH, FRAP value 5.15%, total phenol 18.51 mg gallic acid / 100 ml, total solids 4.75oBrix, and the degree of acidity (pH) 5.65.